Enhanced photocatalytic performance of ZnO nanostructures produced via a quick microwave assisted route for the degradation of rhodamine in aqueous solution. (January 2017) - Thankachan, Rahul Mundiyaniyil; Joy, Nidhin; Abraham, Jiji; Kalarikkal, Nandakumar; Thomas, Sabu; Oluwafemi, Oluwatobi Samuel
Graphical abstract: Highlights: High quality ZnO nanostructures were synthesized by Microwave assisted route. Irradiation time affect the morphology of the as-synthesized ZnO nanorods. Tetrapod and flower-like ZnO nanostructures were produced. All the nanostructures have high photocatalytic capability with superior performance. The high photocatalytic efficiency was maintained after three cycle experiments. Abstract: Water pollution resulting from toxic organic pollutants has become a global issue and identification of a suitable low cost and non-toxic material possessing catalytic behavior is indispensable in order to circumvent this enigma. For solving this problem, we herein report a quick, cost effective, surfactant-free microwave assisted route for the preparation of hexagonal wurtzite ZnO nanostructures and its photocatalytic performances. Structural, morphological and compositional aspects of the nanostructures were determined by various characterization techniques. The photocatalytic efficacies of the samples monitored for the UV induced degradation of aqueous rhodamine B (RhB) solution indicated that all the nanostructures have high photocatalytic capability with superior performance (C/Co) than many existing reports. The highest photocataytic efficiency was obtained for the sample prepared at 0.5 min with 92% efficiency after three cycles experiment and rate constant of 0.042. The possible mechanism for the growth of ZnO nanostructures and photo degradation is also reported.